A contribuição da análise dialógica do discurso para o ensino da escrita escolar: do blog ao artigo de opinião - Bezerra, Symone Nayara Calixto (2018)
Anchored in Dialogical Analysis of Discourse, this work investigates the axiological positioning constructing in school textual productions of high school students based on dialogical actions motivated by the production and handling of a pedagogical blog, mediated by a didactic dialogic planning (PDD), whose reading and discussion route, in classroom, crosses through various discursive genres, culminating in a final product that goes from the discursive genre online commentary to the opinion article. Our general aim was to analyze the construction of axiological positioning in school textual productions of students of the Secondary Education level of a school in the city of Campina Grande - PB based on the process of teaching writing interceded by a dialogical didactic planning (PDD), whose reading route, discussion and writing, in classroom, crosses through several discursive genres and form a great dialogical chain. In order to develop this study, some theoretical contributions are fundamentals: Bakhtin (1983, 2000, 1985, 1975-75), Bakhtin / Volóchinov (1999), Volóchinov (1976, 2016) 2014), Faraco (2001, 2002), Fiorin (2016), Sobral (2009), Geraldi (2006,2013) and others. Based on these contributions, an action-research was realized in a second-year high school class, in the city of Campina Grande - PB. The results reveals that the use of technology in favor of teaching is an excellent strategy for a critical citizen formation, because the dialogic relations created in refracting opinion of the student, in online commentary, in classroom discussions and in articles of opinion, to form a dialogical chain of information and demonstrate how the conditions of writing and dialogical voices, which permeate the writing process, define the construction of the meaning of these enunciations.